A Novel Highly Efficient Device for Growing Micro-Aerophilic Microorganisms - Fuduche, Maxime; Davidson, Sylvain; Boileau, Céline; Wu, Long-Fei; Combet-Blanc, Yannick (Frontiers in Microbiology, 2019)
This work describes a novel, simple, and cost-effective culture system, named Micro-Oxygenated Culture Device (MOCD), designed to grow microorganisms under particularly challenging oxygenation conditions. Two microaerophilic magnetotactic bacteria, a freshwater Magnetospirillum gryphiswaldense strain MSR-1 and a marine Magnetospira sp. strain QH-2, were used as biological models to prove the Micro-Oxygen Culture Device (MOCD) efficiency and to evaluate its specifications. MSR-1 and QH-2 growth rates with the MOCD were respectively increased by 4.0 and 2.0-fold, when compared to the traditional growing techniques using simple bottles. Moreover, the MOCD, which is far less sophisticated than the oxystat-bioreactors specifically designed to control the low O2 concentrations, was proven to be similarly efficient for the MSR-1 and QH-2 cultures regarding growth rate, and even better for MSR-1 regarding the cell yield (rise of 70% rise). Thus, the wide range of oxygenation conditions, including the different O2-gradients, provided by MOCD makes it an innovative and ingenious culture device that opens new perspectives to grow microaerobic microorganisms.